Spatial networks in multi-region computable general equilibrium models - Lofgren, Hans; Robinson, Sherman (International Food Policy Research Institute, 1999)
The spatial dimension of economic policy is often important. However, as opposed to partial-equilibrium multi-region programming models, existing multi-region Computable General Equilibrium (CGE) models have rarely explicitly treated geographical space. This paper develops a spatial-network, mixed-complementarity CGE model that combines the strengths of CGE and partial-equilibrium programming models. We implement the model with a prototype data set for a stylized, poor, developing country with rural regions linked to an urban region that provides the gateway to international markets. We demonstrate that the model provides a good framework for analyzing the impact of higher world prices and reduced domestic transportation costs.